Endodontic microsurgery: An overview - Sumangali Ananad; E Soujanya; Ananda Raju; Aravelli Swathi (Wolters Kluwer Medknow Publications, 2015)
The concurrent development of better techniques has resulted in greater understanding of the apical anatomy, greater treatment success, and a more favorable patient response. These developments marked the beginning of the endodontic microsurgery era that began in the 1990s. There is a substantial difference in surgery outcome between those using the microscope and those do not. Use of advanced technology like a microscope, specially designed instruments, improved root end filling materials help to achieve faster wound healing with lesser postoperative complication.